Expression of sialyltransferases from the St3gal, St6gal and St6galnac families in mouse skeletal muscle and mouse C2C12 myotubes - Milcheva, Rositsa S.; Georgieva, Any K.; Todorova, Katerina S.; Petkova, Svetlozara L. (Acta Biologica Szegediensis, 2022)
In skeletal muscles, the sialic acids have a great significance for their functional maintenance and proper structural organization. Our work described the expressions of St3gal, St6gal and St6galnac sialyltransferases specific for glycoproteins in mouse skeletal muscles and murine C2C12 myotubes. Lectin histochemistry, cytochemistry and lectin blot were used to demonstrate the membrane localization and the electrophoretic profiles of α-2,3- and α-2,6-sialylated glycoproteins. The expression levels of sialyltransferases were analysed by real time RT-PCR and western blot. The enzymes St6gal2 and St6galnac1 were not expressed in skeletal muscle tissue and C2C12 myotubes. In both experimental groups, mRNAs of the St3gal family prevailed over the mRNA expressions of the St6gal and St6galnac families. The profiles of sialyltransferase expressions showed differences between the two experimental groups, illustrated by the absence of expressions of the mRNA for the St3gal6 and St6galnac3 genes in the C2C12 cell samples and by the different shares of the enzymes St3gal3 and St3gal4 in both experimental groups. The different patterns of enzyme expressions in both experimental groups corresponded with differences between their α-2,3- and α-2,6-sialylated glycoprotein profiles. These results could be a useful addendum to the knowledge concerning the glycosylation of the skeletal muscle tissue.